PENGARUH GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN FINANCIAL DISTRESS TERHADAP MANAJEMEN LABA PADA BUMN DI INDONESIA - Wawo, Andi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study examines the influence of Good Corporate Governance (GCG), firm size, and financial distress on earnings management in State-Owned Enterprises (SOEs) in Indonesia, using the agency theory approach. Financial and governance data of SOEs from the 2018–2022 period were analyzed using multiple linear regression. The results indicate that GCG and firm size have a significant negative effect on earnings management. However, financial distress does not influence earnings management. Strong GCG, through the oversight of independent boards of commissioners and audit committees, as well as the strict supervision of large firms, reduces earnings manipulation practices. Additionally, financial difficulties do not drive earnings management, as such difficulties are addressed through state funding injections. These findings underscore the importance of implementing GCG and rigorous oversight to enhance transparency and accountability in SOEs, particularly for smaller SOEs that are more vulnerable.